Integrating gender and social inclusion into behavior change frameworks in agri-food systems: The case of agroecological transformation - Voss, Rachel C.; Freed, Sarah; Rietveld, Anne M.; Falk, Thomas; Adam, Rahma (International Food Policy Research Institute, 2023)
A systems perspective is crucial to understanding behavior-change processes in the agro-ecological transformation of agri-food systems. Systemslevel behavioral frameworks in agricultural systems commonly acknowledge the role of individual demographics, economic and governance factors, and social networks in shaping farmers’, fishers’ and pastoralists’ decisions. However, behaviorchange frameworks rarely account for wider social and relational structures that govern individual and collective behaviors, and are thus relatively gender blind. Social and relational factors are especially relevant to understanding behavior change among women and marginalized groups, whose opportunities and decisions are often constrained by norms and power inequities. We offer a novel conceptual framework for analyzing behavior change in agri-food systems by integrating multidisciplinary behavioral concepts into Ostrom’s social-ecological systems framework. Critical is the notion of ‘opportunity space’, which is here influenced by resource access, social relations, behavioral norms, power and agency. Drawing from experiences in countries engaged in the CGIAR Initiative on Agroecology, we present a case study to illustrate how the framework can be used to more systematically integrate gender relations and equity concerns into behavioral analysis in the context of agri-food systems transformation.